PECULIARITIES OF INTERNAL CONTROL OF COMPANY CALCULATIONS UNDER MARTIAL LAW CONDITIONS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. In the conditions of martial law, enterprises face new challenges that affect all areas of their economic activity, including settlement operations. Internal control of settlements becomes critical for ensuring financial stability and supporting operational activities. This requires a study of the specifics of the organization of internal control of the company's calculations during the state of war, in particular the issue of ensuring the security of financial operations in conditions of instability and market uncertainty.The purpose of the article.  The purpose of the study is to investigate the features and effective mechanisms of internal control of payments at enterprises operating under martial law to ensure their financial stability and competitiveness.Methods. The research methodology includes a comprehensive approach that combines general scientific methods: analysis, synthesis, comparison, as well as specific financial and economic methods of evaluating the internal control system, including methods of risk analysis and auditing of financial operations.Results. The article examines the main principles of ensuring effective internal control of the calculations of economic entities in the conditions of martial law. It was found that failures in the work of banking systems, interruptions in communications and logistics significantly complicate the timely execution of financial transactions. The need to strengthen control over payment discipline on the part of both the enterprise and its counterparties has been identified. The necessity of implementing additional measures to protect the payment system, including increased attention to the verification of counterparties and the use of digital monitoring tools, has been proven. The growing need for rapid adaptation of internal control procedures to new conditions, such as changes in legislation introduced in connection with military operations, or new requirements for financial reporting, which requires the involvement of qualified personnel capable of promptly responding to new challenges and risks, has been studied.Conclusions. It has been proven that the internal control of the company's calculations in the conditions of martial law is an important element of maintaining stable operations and financial security. Therefore, to ensure its effectiveness, it is necessary to constantly update control methods, take into account new risks and challenges associated with war, and implement modern monitoring tools on the basis.
Keywords: internal control, calculations, martial law, financial risks, security of settlement operations, payment discipline.